Study of the Emotional Well-Being of Students in the Process of Education in the Modern School - Meshko, Halyna M.; Meshko, Oleksandr I.; Trubavina, Iryna M. (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
The article is devoted to the current problem of the modern school - the emotional well-being of students in the learning process. The study analyzes the role of the emotional component in students’ learning activities, the impact of emotions on learning outcomes, and the importance of emotional well-being in maintaining and strengthening their health. The purpose of the study was to identify the causes of emotional discomfort of students in the learning process, the ways to ensure the emotional well-being of students, the implementation of which will improve learning success, maintain and strengthen students’ health. The following methods were used to study the state of the emotional well-being of the students: 1) a questionnaire developed by the authors of the research to study the emotional well-being of students at school; 2) the method of assessment of mental activation, interest, emotional tone, tension and comfort, created by L. Kurganskyi and his colleagues; 3) a card to identify factors of learning success. The results of the study showed a low level of the emotional well-being of students in modern schools. Based on the analysis of the study outcomes, the causes of emotional discomfort of students in the learning process are identified. The possibility of improving the effectiveness of learning, educational achievements of students by ensuring their emotional well-being in the learning process is described. Practical ways to improve the emotional well-being of students in the modern school and the formation of their emotional health are outlined and substantiated.